Disordered ferromagnetism in Ho2NiMnO6 double perovskite. (14th November 2016) - Chakraborty, Tirthankar; Nair, Harikrishnan S; Nhalil, Hariharan; Ramesh Kumar, K; Strydom, André M; Elizabeth, Suja
Abstract: Magnetic and dielectric properties of the double perovskite Ho2 NiMnO6 are reported. The compound is synthesized by nitrate route and is found to crystallize in monoclinic P 21 / n space group. Lattice parameters obtained by refining powder x-ray diffraction data are; a = 5.218(2) Å, b = 5.543(2) Å, c = 7.480(3) Å and the monoclinic angle is β = 90.18 ° (4). A phase transition is observed at T C = 86 K in the temperature-dependent magnetization curve, M ( T ). The inverse magnetic susceptibility, (1/ χ ( T ) ) fits reasonably well with modified Curie–Weiss law by incorporating the paramagnetic response of Ho 3+ . 1/ χ ( T ) manifests as an upward deviation from ideal Curie–Weiss behaviour well above the ferromagnetic transition. Signs of inherent Griffiths phase pertaining to the Ni/Mn subsystem are visible when one subtracts the Ho 3+ paramagnetic contribution from total susceptibility and does the power-law analysis. The magnetic hysteresis at 2 K gives the maximum value of magnetization M m a x ≈ 15 μ B /f.u. at 50 kOe. Field-derivative of magnetization at 2 K shows discontinuities which indicates the existence of metamagnetic transitions in this compound. This needs to be probed further. Out of the two dielectric relaxations observed, the one at low temperature may be attributed to phononic frequencies and that at higher temperature may be due to Maxwell–Wagner relaxation. A correlation between magnetic and lattice degrees of freedom is plausible since the anomaly in dielectric constant coincides with T C .